Consensus for heterogeneous multi-agent systems with nonconvex input constraints and nonuniform time delays. Issue 6 (April 2020) - Li, Xue; Li, Cancan; Yang, Yikang; Mo, Lipo
Abstract: In this article, a constrained consensus problem for heterogeneous multi-agent system with nonconvex input constraints and nonuniform time delays was considered. The heterogeneous system is composed of hybrid agents including first-order agents to σ th-order agents, where σ is a positive bounded integer. It is assumed that each agent's control input is constrained to stay in a nonconvex set and the communication topology switches among some digraphs. A new distributed control algorithm is proposed first. And then some sufficient conditions are obtained to ensure the consensus can be reached for the heterogeneous multi-agent system. Finally, we provide the simulation results to verify the feasibility and effectiveness of the proposed algorithm.